Public transportation and sustainability: A review - Miller, Patrick; de Barros, Alexandre G.; Kattan, Lina; Wirasinghe, S. C. (KSCE Journal of Civil Engineering, 2016)
Public transportation is often framed as a key component of building sustainable cities. Conversely, the social, economic, and environmental impacts of transport are framed as critical issues that can challenge the sustainability of cities and regions. This paper presents a critical literature review of the relationship between public transportation and sustainability. First the paper offers a review of key sustainable transportation concepts and how public transport contributes to sustainability goals. Second, the paper reviews past studies that analyse sustainable transportation in order to develop recommendations for planning, engineering, and researching sustainable public transport. Finally, the paper concludes by offering suggestions for future research into the sustainability performance of public transit.